Donor–Acceptor Interactions Induced Interfacial Synthesis of an Ultrathin Fluoric 2D Polymer by Photochemical [2+2] Cycloaddition. Issue 11 (18th January 2021) - Sun, Qingzhu; Pan, Qingyan; Ban, Yanqi; Liu, Hui; Fan, Chunyan; Sun, Lishui; Zhao, Yingjie
Abstract: Two‐dimensional polymers (2DPs) have attracted much interest due to their unique 2D atomic‐thick covalent network with periodically linked monomers. The preparation of mono‐ or few‐layered 2DPs with highly ordered structures is still a big challenge. Herein, we report a preparation of ultrathin 2DP film based on photo‐triggered [2+2] cycloaddition at the air/water interface. The pre‐assembly process induced by the D–A interactions before the polymerization plays a key role in constructing the highly ordered structure. The precise structure and chemical compositions of the continuous 2DP films were proved by selected area electron diffraction (SAED), Tip‐Enhanced Raman Spectroscopy (TERS) and molecular‐mechanics‐based structural simulation. Abstract : An ultrathin 2DP film based on a photo‐triggered [2+2] cycloaddition was prepared at the air/water interface. The pre‐assembly process induced by the D–A interactions before the polymerization plays a key role in constructing the highly ordered structure.